Proceedings of the 31st International Academic Conference, London 2017
DOI: 10.20472/iac.2017.031.032
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wireless Fidelity on Students’ Academic Performance in a Developing Economy

Abstract: Abstract:A wireless technology recently has become our life saver in the communication process and also in sharing of information. Private and public institutions, individuals, businesses, non-profit organisations, government

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This study expects UUM foundation students to work out and concentrate on the most proficient method to set up a suitable internet-based learning condition: adjusting their current educational programs or planning a fresh out of the plastic new one from the beginning. Effective internet-based application devices for internet-based learning convey information successfully, encouraging conversation and complete assignments (Moate, Chukwuere, & Mavhungu, 2017).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…This study expects UUM foundation students to work out and concentrate on the most proficient method to set up a suitable internet-based learning condition: adjusting their current educational programs or planning a fresh out of the plastic new one from the beginning. Effective internet-based application devices for internet-based learning convey information successfully, encouraging conversation and complete assignments (Moate, Chukwuere, & Mavhungu, 2017).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…However, Wi-Fi users gain more advantages compared to data subscription users. The findings of Moate et al (2017) revealed that most students benefit from Wi-Fi in their studies because it enables them to access the internet in various spots, allows them to submit their academic works on time, and enables efficient communication with classmates and lecturers. Students can access information and conduct learning processes through mobile phones, laptops, or even personal computers that can be accessed online (Omar et al, 2018).…”
Section: Internet Connection Sourcementioning
confidence: 99%
“…This study noted a significant increase in internet accessibility at UNIVEN compared to Pearce (1996) who indicated that there was poor internet accessibility at UNIVEN and Maiwashe (2009), who reported that more than 60% of students at UNIVEN did not have regular access to the internet. Having regular access to the internet allows scholars and students at UNIVEN to complete academic tasks on time as suggested by Moate, Chukwuere and Mavhungu (2017). Possible reasons for the increase are an increase in the number of computers purchased by the university; the introduction of hotspot internet connectivity (Wi-Fi); and increased bandwidth.…”
Section: Access To the Internet And Other Ictsmentioning
confidence: 99%
“…Data from Table 3 also show that 102 (49%) postgraduate students use Wi-Fi connectivity while on campus, seventy-eight (38%) used cabled internet and twenty-seven (13%) used a cellular connection. Moate, Chukwuere and Mavhungu (2017) indicated that students welcome the introduction of Wi-Fi and view it as essential to their academic tasks. This study concurs that the available Wi-Fi connection is useful to both scholars and postgraduate students.…”
Section: Internet Connectivitymentioning
confidence: 99%